2007
DOI: 10.1287/isre.1070.0131
|View full text |Cite
|
Sign up to set email alerts
|

Is the World Flat or Spiky? Information Intensity, Skills, and Global Service Disaggregation

Abstract: W hich service occupations are the most susceptible to global disaggregation? What are the factors and mechanisms that make service occupations amenable to global disaggregation? This research addresses these questions by building on previous work by Apte and Mason (1995) and Rai et al. (2006) that focuses on the unbundling of information and physical flows. We propose a theory of service disaggregation and argue that high information intensity makes an occupation more amenable to disaggregation because the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 153 publications
(120 citation statements)
references
References 94 publications
4
114
0
2
Order By: Relevance
“…At the same time, similar to concerns about potentially adverse impacts of offshoring on jobs and wages (Mithas and Whitaker 2007), high-skill immigration also raises issues related to job and wage prospects of foreign and American professionals. Some worry that firms may be exploiting H-1B workers as a source of cheap labor.…”
Section: Prior Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, similar to concerns about potentially adverse impacts of offshoring on jobs and wages (Mithas and Whitaker 2007), high-skill immigration also raises issues related to job and wage prospects of foreign and American professionals. Some worry that firms may be exploiting H-1B workers as a source of cheap labor.…”
Section: Prior Literaturementioning
confidence: 99%
“…Whereas one aspect of globalization relates to outward mobility of work to foreign workers at remote locations as reflected in outsourcing or offshoring of business processes and services (Apte et al 2008, Carmel and Agarwal 2002, DiRomulado and Gurbaxani 1998, Han et al 2010, Lacity et al 2003, Mithas 2008, Mithas and Whitaker 2007, Ramasubbu et al 2008b, Rottman and Lacity 2004), yet another aspect of globalization relates to the inward mobility of foreign workers who are immigrants or on a work visa. The United States admits more than one million immigrants every year, and although a large percentage of these workers have significantly lower skills than native workers (Borjas 2001), some immigrant workers, particularly from Europe and Asia, are highly skilled.…”
Section: Introductionmentioning
confidence: 99%
“…The research also provides the novel methodological utilization of Bayesian structural break models for Poisson data in life cycle research. Finally, the research extends recent research on offshoring of informationintensive services (Mithas and Whitaker 2007) by empirically investigating the heretofore unexamined temporal nature of the offshoring of these services.…”
Section: Implications For Researchmentioning
confidence: 72%
“…Marlin (2005) describes practitioner evidence of this phenomenon, reporting that executives in financial services had indicated that the offshoring of low value-added services was well underway with higher value-added services expected to increasingly follow. From a related perspective, studies of global IT offshoring indicates that lower skilled and more standardized jobs are more easily moved across country borders than are high skill jobs (Aspray et al 2006, Mithas andWhitaker 2007) suggesting that lower skill jobs may be focus of earlier rounds of offshoring. This is in part due to the relative scarcity of higher skilled personnel offshore as well as the difficulty in retention of skilled personnel offshore.…”
Section: Task Skill Level and The Temporal Evolution Of Offshoringmentioning
confidence: 99%
“…More services are being disaggregated globally and delivered from multiple places around the world (Apte and Mason 1995;Mithas and Whitaker 2007). Firms are competing through their extended enterprise and according, to Kanter (1999), a firm's strategic relationships-nurtured by collaboration-are one of the main sources for competitiveness in the 21 st century.…”
Section: Theoretical Foundationsmentioning
confidence: 99%